The Authority of the Judicial Police to Arrest Persons under the Jordanian Criminal Procedure Law in Light of Human Rights Standards - Wejdan Suleiman Irtaimeh (Journal of Humanities and Social Sciences Studies, 2026)
This research aims to analyze the legal framework regulating the judicial of police`s power of arrest individuals under the Jordanian Code of Criminal Procedure authority to determine the extent to which those legal provisions comply with human rights standards and propose amendments to strengthen the legal safeguards governing the exercising of this authority. The research adopted the descriptive method to identify the legal provisions governing the judicial police`s authority to arrest individuals under the Jordanian Code of Criminal Procedure. It also adopted the analytical approach to examine the legal provisions governing the judicial police’s authority to arrest persons and assess their adequacy and propose legislative amendments to ensure a balance between exercising arrest powers and protecting human rights. Additionally, the comparative method was adopted in some parts, by comparing certain legal provisions governing arrest with comparative legislation, as well as with international human rights instruments and agreements. The research identified several important findings, with the principal finding being that the Jordanian Code of Criminal Procedure includes several procedural safeguards regulating the judicial police`s authority in arresting individuals, which has contributed to achieving a degree of balance between the exercise of this authority and protection human rights. However, it does not provide certain procedural safeguards for individuals arrested by the judicial police, including the right to be informed of the grounds for the arrest, obtaining legal assistance, the right to remain silent, and the right to receive medical assistance. The research concluded that amendments to the Jordanian Code of Criminal Procedure are necessary and explicitly stipulate some procedural safeguards for the persons arrested by the judicial police during the execution of arrest.